Traditional Chinese Medicine Ion Introduction Therapy Reduces the Incidence of Acute Exacerbation of Idiopathic Pulmonary Fibrosis: A Prospective Cohort Study - Wang Y; Xu B; Wang J; Li S; Xie Y (International Journal of General Medicine)
Yan Wang,1,2 Baichuan Xu,1,2 Jiajia Wang,1,3,4 Suyun Li,1,3,4 Yang Xie1,3,4 1National Regional Traditional Chinese Medicine (Lung Disease) Diagnosis and Treatment Center, The First Affiliated Hospital of Henan University of Chinese Medicine, Zhengzhou, Henan, 450046, People’s Republic of China; 2The First Clinical College of Henan University of Traditional Chinese Medicine, Zhengzhou, Henan, 450000, People’s Republic of China; 3Henan University of Traditional Chinese Medicine Respiratory Disease Diagnosis and Treatment and New Drug Research and Development Provincial and Ministry Co-Built Collaborative Innovation Center, Zhengzhou, Henan, 450046, People’s Republic of China; 4Henan Key Laboratory of Traditional Chinese Medicine for Prevention and Treatment of Respiratory Diseases, Zhengzhou, Henan, 450046, People’s Republic of ChinaCorrespondence: Yang Xie; Suyun Li, Email xieyanghn@163.com; lisuyun2000@126.comObjective: To evaluate the effectiveness and safety of traditional Chinese medicine (TCM) ion introduction therapy in the treatment of patients with acute exacerbation of idiopathic pulmonary fibrosis (AE-IPF).Methods: This study adopts a prospective cohort study design, with 60 AE-IPF patients as the research subjects. Divided into an exposed group and a non exposed group, with 30 cases in each group, based on the frequency of TCM ion introduction treatment as the exposure factor. Follow-up for 1 year to observe the acute exacerbation of the patient. The main indicator is the annual incidence of acute exacerbation, and the secondary indicators are hospitalization time, readmission rate, time to first acute exacerbation, mortality rate, all-cause mortality rate, inflammatory indicators, quality of life, etc.Results: 51 patients completed a one-year clinical observation, including 27 in the exposed group and 24 in the non exposed group. Compared to the non exposed group, significant differences were observed in the annual incidence of acute exacerbation [incidence rate ratios (IRR) = 0.556, 95% CI: 0.315, 0.980; P = 0.035] and hospitalization time (P = 0.040), readmission rate (IRR = 0.533, 95% CI: 0.288, 0.988; P = 0.037), time to first acute exacerbation (P = 0.045), and quality of life (P < 0.05). However, there was no statistically significant difference in mortality rate and all-cause mortality rate between the two groups (P > 0.05).Conclusion: Compared to the non exposed group, TCM ion introduction can reduce the annual incidence of acute exacerbation of IPF patients. Hospitalization time, readmission rate, time to first acute exacerbation, quality of life improved, but mortality rate and all-cause mortality rate did not improve.Keywords: TCM, ion introduction, idiopathic pulmonary fibrosis, acute exacerbation, incidence